Development of a Core Outcome Set for Dysphagia Interventions in Parkinson's disease (COS-DIP) - Regan, Julie; Walshe, Margaret (My University, 2024)
Introduction: Current clinical trials on swallowing disorders (dysphagia) in Parkinson's disease (PD) apply a high variety of outcomes and different outcome measures making comparative effectiveness research challenging. Furthermore, views of patients and dysphagia clinicians when selecting trial outcomes have not been considered in the past, thus study results may have little importance to them. This study aims to develop an agreed standardised Core Outcome Set for Dysphagia Interventions in Parkinson's disease (COS-DIP), systematically measured and reported as a minimum for all clinical trials. It will also comprise guidance on outcome definitions, outcome measures and time points of measurement. Methods and analysis: The COS-DIP development will comprise five stages following established methodology: (1) a recent scoping review on all applied outcomes, their definitions, methods and time points of measurement in clinical trials in dysphagia in PD, (2) online surveys and focus groups with clinicians, patients, caregivers and family members to identify outcomes that are important to them, (3) an identified list of outcomes based on results of stage 1 and 2, (4) three round online Delphi survey with up to 200 key stakeholders to determine core outcomes and (5) two online consensus meetings with up to 40 representative key stakeholders to agree on all outcomes, definitions, methods and time points of measurement in the final COS-DIP. Ethics and dissemination: Full ethical approval was obtained from the Research Ethics Committee, School of Linguistic, Speech and Communication Sciences, Trinity College Dublin, on 15 May 2023 (HT27). Dissemination of the COS-DIP will be enhanced through presentations at (inter-) national conferences and through peer-reviewed, open access publications of related manuscripts. Lay and professional information sheets and infographics will be circulated through relevant patient and professional organisations and networks. Trial registration number: The COS-DIP study was registered prospectively with the Core Outcome Measures in Effectiveness Trials (COMET) database on 24 September 2021 (www.comet-initiative.org/Studies/Details/1942).
PUBLISHED
Keywords: Clinical trials; Parkinson-s disease; REHABILITATION MEDICINE; Ageing; Inclusive Society; CLINICAL TRIALS; DYSPHAGIA; Swallowing Disorders; Age-related disability; Chronic Health Condition; Health